Sounds of senescence: male swamp sparrows respond less aggressively to the songs of older individuals. (7th January 2020) - Zipple, Matthew N; Peters, Susan; Searcy, William A; Nowicki, Stephen
Abstract: Age-related changes in assessment signals occur in a diverse array of animals, including humans. Age-related decline in vocal quality in humans is known to affect perceived attractiveness by potential mates and voters, but whether such changes have functional implications for nonhuman animals is poorly understood. Most studies of age-related change in animal signals focus on increases in signal quality that occur soon after the age of first breeding ("delayed maturation"), but a few have shown that signal quality declines in older individuals after a mid-life peak ("behavioral senescence"). Whether other individuals are able to detect this senescent decline of assessment signals has not previously been tested. Here we use playback experiments to show that wild male swamp sparrows ( Melospiza georgiana ) respond more aggressively to songs from 2-year-old males as compared with songs from the same males when they are 10 years old. Senescence in signals that, like birdsong, affect reproductive success through intrasexual competition or mate choice may be of evolutionary significance. Abstract : Using playback experiments with wild swamp sparrows ( Melospiza georgiana ), we demonstrate that listeners both detect and respond to age-related declines in vocal quality. Two previous studies have shown that some song characteristics deteriorate with age later in life in songbirds, but to our knowledge this is the first demonstration outside of humans that such deterioration affects receiver response. Discrimination of songs from males of different ages may have evolutionary implications.